Stock Split in Insider Trading: Lessons from Malaysia - Shaharudin, Jakpar; Michael, Tinggi; Tan, Zhao Yu; Norshamsiah, Samsudin (HRMARS, 2020)
Average daily cumulative abnormal volume turnover (ACAVT) is an interesting indicator for research purposes to determine the existence of possibly insider trading. The objective of this paper is to examine the existence of the possibly insider trading prior stock split announcement by using ACAVT. A sample of 79 public listed companies in Bursa Malaysia which did stock split within the period of 2013 to 2017 is analyzed. This paper also studies sample with positive ACAVT to determine the relationship between insider trading and independent variables which are market capitalization and major shareholder. One Sample T-Test and Multiple Regression Analysis are used in the study. The results indicate that there is 36.71% or 29 of studies sample involved in suspicious of insider trading. However, the negative value of ACAVT’s mean indicates that there is no existence of possibly insider trading prior stock split announcement. Market capitalization and major shareholder are insignificant negatively associated with possibly insider trading.